2007
DOI: 10.31901/24566772.2007/01.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Tradition Vs Transition: Acceptance of Health Care Systems among the Santhals of Orissa

Abstract: Medical anthropology looks at cultural conceptions of the body, health and illness. Medical anthropology is the study of ethno-medicine; explanation of illness and disease; what causes illness; the evaluation of health, illness and cure from both an emic and etic point of view; naturalistic and personalistic explanation , evil eye, magic and sorcery; biocultural and political study of health ecology; types of medical systems; development of systems of medical knowledge and health care and patient-practitioner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Thus pregnant mothers suffer malnutrition; their babies too suffer from vitamin deficiency and become rickety. Sonowal and Praharaj (2007, p. 139) also mention the same findings in most of Indian tribes. They have a negative attitude towards cesarean delivery as they believe that after delivery they will need to take rest for a longer time period which will affect their household chores and other family responsibilities.…”
Section: Antenatal Caresupporting
confidence: 58%
“…Thus pregnant mothers suffer malnutrition; their babies too suffer from vitamin deficiency and become rickety. Sonowal and Praharaj (2007, p. 139) also mention the same findings in most of Indian tribes. They have a negative attitude towards cesarean delivery as they believe that after delivery they will need to take rest for a longer time period which will affect their household chores and other family responsibilities.…”
Section: Antenatal Caresupporting
confidence: 58%
“…Modern health-care practitioners attribute most of the diseases among tribal people to regular drinking habits, but tribal people perceive it in other ways. Santals believe that rice beer provides the required energy to work in their respective fields (Sonowal & Praharaj, 2007). Thus, poor nutritious food intake and the consumption of rice beer on a regular basis contribute negatively to the health of the studied population.…”
Section: Cultural Factorsmentioning
confidence: 98%
“…5 Like many other tribes, the Santals believe in four types of supernatural powers-the benevolent spirit (which includes worship in the family and community level regularly for a healthy life), the protective spirit (which prevents them from ill occurrence), the malevolent spirit (an evil spirit which controls all kinds of diseases in the community) and the ancestor spirit (Sonowal & Praharaj, 2007). The Santals have their own village council which includes a headman (majhi haram), an assistant headman (jog-majhi), a priest (nacke) and a messenger (godet) (Sonowal & Praharaj, 2007). The village council has greater influence on illnesses and the management of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The need for such concern arises due to customs and traditions that are related to sexual behavior and child bearing. Studies have revealed that there are practices among some tribes of limiting the consumption of food from sixth month of pregnancy with an intention of making the process of delivery easy (Sonowal &Praharaj 2007) . Anemia is rampant among women (especially among the pregnant women) which causes not only slowness in the development of the foetus but also causes mental retardedness-thus raising morbidity and mortality among tribal women and children (Singh 2008: 120).…”
Section: Introductionmentioning
confidence: 99%